HER2-Testung beim Magenkarzinom: Ergebnisse eines deutschen Expertentreffens = HER2 testing in gastric cancer : results of a meeting of German experts - Baretton, Gustavo Bruno; Gaiser, Timo; Hofheinz, Ralf-Dieter (Der Pathologe, 2016)
Valid HER2 testing is essential for the optimal care of patients with HER2-positive gastric cancer and the correct use of first-line treatment. Although all cases of breast cancer are routinely tested for the HER2 status, HER2 testing in gastric cancer has still not become part of the routine and is usually only done upon request by the therapist. An interdisciplinary group of German experts has taken on the challenges of HER2 testing in gastric cancer as an opportunity to address essential aspects and questions on the practical use of HER2 testing in this indication from the perspective of pathologists and therapists. The recommendations made in this article reflect the consensus of all participants and correspond to their opinions and long-term experience.
Gesehen am 02.07.2019